Hemoglobina glucosilada >=7.5% como factor de riesgo de infarto agudo de miocardio en pacientes con diabetes mellitus tipo 2 - Aburto Moreno, Maycol Leonardo (2017)
Introduction: There have been several studies in order to establish the relationship of chronic complications of type 2 diabetes mellitus (DM2) and glycemic control, seeing that until now the value of measuring the levels of Glycosylated hemoglobin (HbA1c) for predicting first cardiovascular events are uncertain. Objective: Determine whether HbA1c ≥ 7.5% is a risk factor for acute myocardial infarction (AMI) in patients with Type 2 Diabetes Mellitus. Methods: was used a study of cases and controls, was conducted with a random sample of 162 patients attended in the Internal Medicine and Cardiology service of the Regional Teaching Hospital of Trujillo (HRDT) and Belen Hospital of Trujillo (HBT) (81 cases and 81 controls). Logistic regression was used to estimate the odds ratio (OR) and confidence intervals 95% (95% CI) for relationship between HbA1c and risk of AMI. Results: The ratio of the presentation of AMI in patients with DM2 was 3.45 times greater in diabetics with Hb1AC≥7.5% compared to diabetics with HbA1C <7.5% (OR= 3.45, IC 95%: 1.8 – 6.5 and p <0.05). In addition, patients with DM2 who presented AMI with an HbAc1≥7.5% were 70.3% (ratio of 2,375 to 1, men versus women); compared to 40.7% in patients with DM2 who did not present AMI with HbAc1 ≥ 7.5%. Conclusion: HbA1c ≥ 7.5% itself is a risk factor for AMI in patients with DM2